DEVELOPMENT OF GENERAL AND SPECIAL PHYSICAL QUALITIES OF 15-16 YEAR OLD VOLLEYBALL PLAYERS THROUGH SPORTS SECTION TRAINING (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The article discusses the methodology of developing general physical qualities in 15-16-year-old volleyball girls through volleyball training. At this age, the basic physical parameters that need to be developed, such as strength, endurance, speed, flexibility and coordination, are studied. Special exercises and educational programs aimed at increasing these qualities, as well as recommendations for organizing the educational process, are described.